From ICT outsourcing to strategic sourcing: managing customer?supplier relations for continuous innovation capabilities. (30th April 2008) - Ciappini, Alessia; Corso, Mariano; Perego, Alessandro
This paper aims to provide interpretative and empirical models to describe the evolution and management of ICT Outsourcing relations in terms of different typologies of sourcing model, governance mechanisms and the impact on Continuous Innovation (CI) capabilities. The work is based on an empirical study involving 40 cases and a survey on 70 enterprises. Managerial implications and relevant models and evidence derived from the sample support practitioners in identifying the suitable sourcing models, in defining the right mix of governance levers to be used, in understanding the typical evolution of outsourcing relations and in discovering the variables that can impact on the quality of the relation over time.